Nepal’s Proportional Representation System: An Analysis of Its Misuse and Impact - Thapa, Santa Bahadur (Cognition, 2026)
Nepal’s 2015 Constitution introduced Proportional Representation (PR) with the expectation of allowing more socially excluded groups to participate in politics. This paper argues that chronic systemic abuse has rendered the PR system virtually ineffective at translating numerical representation into political power. To understand this failure, take a hard look at the structural weaknesses of democracy in Nepal. The methodology utilizes a reflexive synthesis of post-2015 voting data and literature, within the context of an Inclusion Effectiveness Gap model, to understand operational diversity. The important point is that the number of diversified counterparties and political weight are not in proportion. The gap is blamed on two main mechanisms: flawed internal party democracy, in which an elite picks candidates for loyalty and money; and corrosive external geopolitical competition from the neighbours, which intensifies ethnic and regional inequalities. The bottom line is that the PR system is fundamentally broken and needs systemic electoral reform. The originality of the study lies in thoroughly combining internal partisan corruption and external geostrategic influence as disabling elements of the system, thereby delivering real, decisive power to specific legislative interventions.